PENGARUH PENENTUAN HARGA POKOK PRODUKSI TERHADAP HARGA JUAL PADA INDUSTRI KRUPUK (Studi Kasus di UD. INUN JAYA Sampang) - waryanto, r. bambang dwi; Nasrulloh, Nasrulloh (Fakultas Ekonomi Universitas PGRI Adi Buana, 2014)
This study was conducted to determine how much influence the Cost of Production Against Selling Price At UD. INUN JAYA Sampang. The method used in this research is descriptive method of analysis and testing hepotesis t test, through data collection techniques, documentation, and literature containing data on the cost of production and selling price as well as other support during the period 2007 - 2013 which is based on the company. The sampling technique used is probability sampling with a random sampling approach. The purpose of this sampling is to determine how much influence the cost of production to the selling price.The variables were tested for the cost of production as the independent variable (X) and the sale price as the dependent variable (Y). and hypothesis testing can proceed. Meanwhile, to test the hypothesis used simple linear regression to determine how much influence the variable X to variable Y, and t test is used to determine the level of significance between the independent variable (X) is the cost of production to the dependent variable (Y) that is selling price.The conclusion of this study, Ho is rejected and Ha is accepted, it means the cost of production has positive influence on the selling price.